Cardiovascular magnetic resonance - Manning, Warren J.; Pennell, Dudley J., 1958-; Manning, Warren J. (Philadelphia, PA : Saunders/Elsevier, 2010)
'Cardiovascular Magnetic Resonance provides you with up-to-date clinical applications of cardiovascular MRI for the broad spectrum of cardiovascular diseases, including ischemic, myopathic, valvular, and congenital heart diseases, as well as great vessel and peripheral vascular disease. Editors Warren J. Manning and Dudley J. Pennell and their team of international contributors cover everything from basic MR physics to sequence design, flow quantification and spectroscopy to structural anatomy and pathology. Learn the appropriate role for CMR in a variety of clinical settings with reference to other modalities, practical limitations, and costs. With the latest information on contrast agents, MR angiography, MR spectroscopy, imaging protocols, and more, this book is essential for both the beginner and expert CMR practitioner.'--Publisher's website.
Basic Principles of Cardiovascular Magnetic Resonance -- Ischemic Heart Disease -- Right Ventricular and Congenital Heart Disease -- Vasculature and Pericardium -- Functional Cardiovascular Disease -- Analogous CMR TerminologyUsed by Various Vendors -- CMR Screening FormBeth IsraelDeaconess Medical CenterCMR Center -- CMR Worksheet and Sequence ProtocolDataform in use 2010 at the BethIsrael Deaconess Medical CenterBIDMCCMR Center.
Rev. ed. of: Cardiovascular magnetic resonance / Warren J. Manning, Dudley J. Pennell. 1st ed. 2002.
In Process PDAL
Includes bibliographical references and index.
Keywords: Cardiovascular diseases -- Diagnosis; Magnetic Resonance Imaging -- methods; Diagnostic Techniques, Cardiovascular; Heart -- Magnetic resonance imaging